Processo de mudança em psicoterapia psicanalítica - Cassel, Paula Argemi (2014)
The research in the psychotherapy process studies how change occurs throughout the treatment. Its examination comprises the psychotherapeutic interaction and the important moments of change lived by the patient. These elements are supplied by the objective appointments taken at the psychotherapeutic sessions. In this context the objective of this study was to examine the moments of change in psychoanalytic psychotherapy. Two studies were carried out. One theoretical and one empirical, presented as two sections. The theoretical section describes, through a non-systematic review of the literature about research in psychotherapy. Also presents what comprises in psychoanalytic psychotherapy and the based in evidence research characteristics of the psychotherapy. The empirical section examined moments of change in psychoanalytic psychotherapy trough the analyses of three sessions, representing the beginning, the middle and the end of treatment: the first, the twelfth and the eighteenth of a set of 21 sessions of psychoanalytic psychotherapy. The design was the systematic case study (ECS) with a qualitative and naturalistic single-case methodology. In order to achieve this, it was utilized the Adherence to Psychoanalytic Technique Instrument (APT-I) to verify the adherence of each psychotherapeutic session to the psychoanalysis technique and to guarantee that the psychotherapeutic process really took place as a psychoanalysis psychotherapy. It was utilized also the Therapeutic Cycles Model (TCM) instrument in the identification of the moments of change in the therapeutic process through the language patterns of the psychotherapist and patient, taken from demarcation of the therapeutic cycles, which have associations to the idea of progress in the therapeutic process. It was found at the first session, four therapeutic cycles, three therapeutic cycles in the twelfth session and two cycles in the eighteenth session. The verbalizations of psychotherapist and patient in the therapeutic cycles were examined through its content analysis. Afterwards, each psychotherapeutic session was discussed taking into account the psychoanalysis theory together with the evaluation of the adherence to the psychoanalytic technique by the APT-I. The results allow us to conclude that the combination of objective measurements, derived from the cycle analysis by the TCM and the evaluation of adherence to the psychoanalytic technique by the APT-I, associated to the psychodynamics understanding of changes give us a profound apprehension of the case, especially the movements in the patient psychotherapist pair regarding to changes on the patient.